Good economics for hard times - Banerjee, Abhijit V., 1961- (Juggernaut Books, 2019)
"Figuring out how to deal with today's critical economic problems is perhaps the great challenge of our time. Much greater than space travel or perhaps even the next revolutionary medical breakthrough, what is at stake is the whole idea of the good life as we have known it. Immigration and inequality, globalization and technological disruption, slowing growth and accelerating climate change--these are sources of great anxiety across the world ... The resources to address these challenges are there--what we lack are ideas that will help us jump the wall of disagreement and distrust that divides us. If we succeed, history will remember our era with gratitude; if we fail, the potential losses are incalculable. In this ... book, renowned MIT economists Abhijit V. Banerjee and Esther Duflo take on this challenge"--Publisher's description.